Die Thalliumszintigraphie des Myokards - Fritzsche, H.; Bergmann, H.; Fridrich, L.; Köhn, H.; Lind, P.; Mlczoch, J.; Mostbeck, A.; Porenta, G. (Nuklearmedizin - NuclearMedicine, 1995)
Zur Vermeidung von Interpretationsschwierigkeiten der verschiedenen Untersuchungsprotokolle und von Wiederholungsuntersuchungen der Thalliumszintigraphie des Myokards wurde ein für Österreich einheitliches Untersuchungsprotokoll erarbeitet. Ab 1.1. 1995 wird dieses Untersuchungsprotokoll zum Einsatz kommen, Abweichungen von diesem Protokoll müssen besonders vermerkt werden. Es werden der Untersuchungablauf, die Belastungsmethoden mit dem Ergometer und mit pharmakologischen Substanzen, die Aufnahmetechnik der planaren und SPECT-Szintigraphie, die Auswertemethoden und die Qualitätskontrolle der Geräte festgelegt.A uniform protocol for thallium scintigraphy of the myocardium has been issued in Austria to avoid difficulties in interpreting results and to avoid repeated examinations to save expenses and radiation burden. From the beginning of 1995 this protocol will be used in the Austrian departments of Nuclear Medicine, differences from this protocol have to be mentioned separately. In this protocol the procedure of examination. bicycle and pharmacological stress testing and vasodilatation, acquisition techniques for planar and SPECT imaging, data processing and quality control of devices are defined.